Time-bandwidth problem in room temperature slow light - Ooi, Chong Heng Raymond; Scully, M.O.; Deng, Z.J.; Qing, D.K.; Hemmer, P.; Zubairy, M.S. (2006)
For many applications of slow or stopped light, the delay-time-bandwidth product is a fundamental issue. So far, however, slow-light demonstrations do not show a large delay-time-bandwidth product, especially in room temperature solids. Here we demonstrate that the use of artificial inhomogeneous broadening has the potential to solve this problem. A proof-of-principle experiment is done using slow light produced by two-beam coupling in a photorefractive crystal CeBaTiO3 where Bragg selection is used to provide the artificial inhomogeneity. Examples of how to generalize this concept for use with other room temperature slow-light solids are also given.